Brain natriuretic peptide and right heart dysfunction after heart transplantation. Issue 6 (16th April 2017) - Talha, Samy; Charloux, Anne; Piquard, François; Geny, Bernard
Abstract: Heart transplantation (HT) should normalize cardiac endocrine function, but brain natriuretic peptide (BNP) levels remain elevated after HT, even in the absence of left ventricular hemodynamic disturbance or allograft rejection. Right ventricle (RV) abnormalities are common in HT recipients (HTx), as a result of engraftment process, tricuspid insufficiency, and/or repeated inflammation due to iterative endomyocardial biopsies. RV function follow‐up is vital for patient management as RV dysfunction is a recognized cause of in‐hospital death and is responsible for a worse prognosis. Interestingly, few and controversial data are available concerning the relationship between plasma BNP levels and RV functional impairment in HTx. This suggests that infra‐clinical modifications, such as subtle immune system disorders or hypoxic conditions, might influence BNP expression. Nevertheless, due to other altered circulating molecular forms of BNP, a lack of specificity of BNP assays is described in heart failure patients. This phenomenon could exist in HT population and could explain elevated BNP plasmatic levels despite a normal RV function. In clinical practice, intra‐individual change in BNP over time, rather than absolute BNP values, might be more helpful in detecting right cardiac dysfunction in HTx.